A novel tube model predictive control for surge instability in compressor system including piping acoustic. Issue 1 (1st January 2017) - Imani, Hashem; Jahed-Motlagh, Mohammad Reza; Salahshoor, Karim; Ramezani, Amin; Moarefianpur, Ali
Abstract: Tube model predictive control (MPC) is one of a few suitable techniques for robust stabilization of disturbed nonlinear systems subject to constraints. This paper introduces the integration of H ∞ control scheme into a robust tube MPC control algorithm for surge prevention in centrifugal compressor system in the presence of bounded disturbances. Nonlinear dynamic of compression system is considered that contains acoustic of compressor system and brings up the effects of the station's piping system on the compressor surge. Also, close-coupled valve is selected as actuator for the surge control system. The proposed method is composed of two controllers: a nominal MPC controller which solves a standard surge problem for the nominal system, and an ancillary MPC controller from H ∞ control approach to stabilize the states despite disturbances. Numerical simulation results verify the capability of the proposed surge control method and guaranty the asymptotic stability of compression system in the presence of disturbances.